Exploring the Spiritual and Functional Aspects of Sacred Groves: An Ecological Case Study of the Kwaékese and Twendurase Mystical Sacred Groves in Ghana - Asante, Daniel Boamah (Worldviews, 2024)
This study delves into the multifaceted nature of sacred groves within the Kwahu Traditional Area of Ghana, specifically focusing on the Kwaékese and Twendurase Mystical Sacred Groves. These groves represent unique community-conserved areas, intertwined with both spiritual and utilitarian motives. Simultaneously, the study delves into their ecological role in safeguarding perennial water sources and as repositories for endangered flora and fauna, preserving biodiversity in the face of expanding human activities. Furthermore, the research highlights the evolving role of sacred groves in response to contemporary challenges, such as population growth and deforestation. This study underscores the coexistence of spirituality and practicality in these unique ecosystems, shedding light on the multifaceted nature of sacred groves and their indispensable ecological significance.